Autoimmune Hemolytic Anemia as Presenting Symptom of Hodgkin Lymphoma. (31st March 2021) - Burley, Nicholas B.; Dy, Paul S.; Hande, Suraj; Kalantri, Shreyas; Mohindroo, Chirayu; Miller, Kenneth
Abstract : Autoimmune hemolytic anemia (AIHA) is related to an underlying condition in an estimated 50 to 60%, while the remaining is idiopathic, as a result of a combination of immune activation, deficiency, or dysregulation. AIHA is associated with viral infections, autoimmune disorders, immunodeficiencies, lymphoproliferative disorders, and pregnancy. AIHA has predictive properties and may be a harbinger of future lymphoproliferative disorders in up to 20% of AIHA cases. Autoimmune hemolytic anemia (AIHA) has been associated with lymphoproliferative disorders particularly chronic lymphocytic leukemia and non-Hodgkin lymphoma. Rarely is it seen in Hodgkin disease. In the following report, we describe the presentation of AIHA, ultimately resulting in the diagnosis of nodular sclerosis Hodgkin lymphoma (stage III). From the limited reports and reviews available, it is understood that advanced Hodgkin (stage III or IV) of nodular sclerosis (NS) or mixed cellularity (MC) types portend a stronger affiliation to AIHA. The majority of AIHA-associated Hodgkin lymphoma presents as stage III or IV disease with the hemolysis being the presenting symptom, as in this case. The mainstay of AIHA therapy has been corticosteroids; however, this first-line regimen appears to be less effective when treating AIHA in the setting of HL. The exact mechanism of AIHA related to HL is unclear, and it may be thought to be that tumor cell produced autoantibodies. Other hypotheses include paraneoplastic phenomena or more, perhaps immunity to tumor cells may cross-react with antigens on the red cells. Although these mechanisms require further investigation, the relationship of the AIHA and HL represents a piece to a larger puzzle between autoimmune disorders and lymphoproliferative conditions.